2004
DOI: 10.1262/jrd.50.481
|View full text |Cite
|
Sign up to set email alerts
|

Improved Survival of Vitrified In Vivo-Derived Porcine Embryos

Abstract: Abstract. An efficient cryopreservation protocol for porcine morulae was investigated with three types of vitrification having different cooling rates (Exp. 1). Survival of embryos vitrified after removal of cytoplasmic lipid droplets was also examined by means of the minimum volume cooling (MVC) method (Exp. 2). In Exp. 1, the morula stage embryos were vitrified with a 0.25 ml plastic straw (ST-method), gel loading tip (GLT-method) and the MVC-method, respectively, and stored in liquid nitrogen after which th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
24
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 16 publications
3
24
0
1
Order By: Relevance
“…We have also confirmed in our previous studies that delipation of porcine in vitro-produced embryos at the morula stage is less injurious than when done at the early cleavage stages or the blastocyst stage [16][17][18][19]. In addition, it was shown that vitrification of delipated porcine embryos at the morula stage results in a high postwarming survival rate [16,18,19]. In conjunction with these studies, we carried out a study of the vitrification of porcine cloned embryos at the morula stage.…”
supporting
confidence: 80%
“…We have also confirmed in our previous studies that delipation of porcine in vitro-produced embryos at the morula stage is less injurious than when done at the early cleavage stages or the blastocyst stage [16][17][18][19]. In addition, it was shown that vitrification of delipated porcine embryos at the morula stage results in a high postwarming survival rate [16,18,19]. In conjunction with these studies, we carried out a study of the vitrification of porcine cloned embryos at the morula stage.…”
supporting
confidence: 80%
“…The Cryotop method requires a maximum microdroplet volume of 0.1 µl of vitrification solution [13]. The Cryotop method is very effective for cryopreserving embryos and has been used in various mammalian species, including humans [19,32], cattle [28], mice [33], pigs [34,35] and rabbits [36]. Thus, it is appropriate to consider the 0.1 µl maximum volume as standard for MVC methods.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the number of embryos that can be vitrified in one operation has been limited. Ushijima et al [4] reported that the MVC method allows simultaneous vitrification of 8 to 12 embryos. In pigs, it is desirable to cryopreserve larger numbers of embryos together because 15 to 20 embryos should be transferred into a recipient at one time.…”
Section: Discussionmentioning
confidence: 99%
“…In Method 2, the MVC method was conducted using a Cryotop ® and commercial vitrification and warming solutions (VT101 and VT102, Kitazato BioPharma, Shizuoka, Japan) by the method previously reported [3,4]. The embryos were contracted by dehydration in an equilibration solution (ES of VT101, Kitazato BioPharma) and kept at room temperature (25 C) for 5 to 10 min until they regained their volume to some extent.…”
Section: Vitrification and Warming Of Embryosmentioning
confidence: 99%
See 1 more Smart Citation